Overcoming polymorphism: a revised list of shell characters for the phylogenetic analysis of soft-shelled turtles (Pan-Trionychidae) - Walter G. Joyce (Swiss Journal of Palaeontology)
Abstract Soft-shelled turtles (Pan-Trionychidae) are one of the primary clades of turtles with a particularly rich fossil record reaching back to the Early Cretaceous. Yet, the evolution of the group has been difficult to resolve, in part because the fossil record mostly consists of shells and because the shells are known to exhibit high levels of polymorphism, making it difficult to establish parsimony-informative characters. A revision of the shell osteology of extant and extinct pan-trionychid turtles resulted in the development of 69 revised and novel characters with over 221 derived character states. Of these, 40 are multistate characters and 11 morphometric characters that utilize length, surface, and angular measurements. In a first step, the characters were scored for 530 regularly developed individuals representing all currently recognized species of living trionychids. The primary dataset confirms that most characters are affected by high levels of polymorphism. Statistical analyses conclude that much variability can be attributed to ontogenetic changes. In a second step, the primary data was used to code terminal taxa by reference to the most adult individuals for characters controlled by ontogeny. Terminals were otherwise only scored polymorphic if at least 20% of individuals displayed a particular character state. A phylogenetic analysis concludes that the new characters converge best upon the emerging molecular consensus, if characters are run ordered. All three utilized outgroups have a negative impact on ingroup relationships and character evolution, which can only partially be addressed through the use of a molecular backbone. The reduction of polymorphism by reference to adults and a minimum frequency of 20% yields more parsimony-informative characters and character states. A brief account is provided on how to diagnose all extant clades and species of trionychids using osteological characters.